2023
DOI: 10.1111/2041-210x.14073
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing insect metabarcoding using replicated mock communities

Abstract: Metabarcoding (high‐throughput sequencing of marker gene amplicons) has emerged as a promising and cost‐effective method for characterizing insect community samples. Yet, the methodology varies greatly among studies and its performance has not been systematically evaluated to date. In particular, it is unclear how accurately metabarcoding can resolve species communities in terms of presence‐absence, abundance and biomass. Here we use mock community experiments and a simple probabilistic model to evaluate the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 71 publications
(81 reference statements)
0
16
0
Order By: Relevance
“…Firstly, our approach is a compromise between improving feasibility for large-scale monitoring and the chances of detecting all taxa. Additional sample processing, such as complementary mild lysis (Marquina et al 2022, Iwaszkiewicz-Eggebrecht et al 2023), greater replication (Zizka et al 2022b) and using multiple gene markers or primers (Elbrecht et al 2019, Hajibabaei et al 2019), as well as increasing sequencing depth (this study), would undoubtedly recover more species. However, the additional effort required must be weighed against the extra information gained, which may not be substantial (Buchner et al 2021a) Secondly, the incompleteness of regional and interregional reference sequence databases, and the generation of reference sequences of unknown species, remains a persistent challenge (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, our approach is a compromise between improving feasibility for large-scale monitoring and the chances of detecting all taxa. Additional sample processing, such as complementary mild lysis (Marquina et al 2022, Iwaszkiewicz-Eggebrecht et al 2023), greater replication (Zizka et al 2022b) and using multiple gene markers or primers (Elbrecht et al 2019, Hajibabaei et al 2019), as well as increasing sequencing depth (this study), would undoubtedly recover more species. However, the additional effort required must be weighed against the extra information gained, which may not be substantial (Buchner et al 2021a) Secondly, the incompleteness of regional and interregional reference sequence databases, and the generation of reference sequences of unknown species, remains a persistent challenge (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For this work, we chose a non-destructive approach for the DNA extraction from the bulk samples, as we were interested in keeping the individual arthropods for further morphological analysis. A series of recent studies have tested the suitability of these non-destructive DNA extraction protocols, finding them as a promising alternative to sample homogenization in terms of biodiversity detection (Batovska et al, 2021;Iwaszkiewicz-Eggebrecht et al, 2023;Marquina et al, 2022;Nielsen et al, 2019). However, there may be limitations relevant for the analysis of our samples: for instance, both Iwaszkiewicz-Eggebrecht et al (2023) and Marquina et al (2022) found that ants (Hymenoptera: Formicidae) were detected in their mock communities in much lower proportion and occasions than other taxa.…”
Section: Biodiversity Detectionmentioning
confidence: 99%
“…A series of recent studies have tested the suitability of these non-destructive DNA extraction protocols, finding them as a promising alternative to sample homogenization in terms of biodiversity detection (Batovska et al, 2021;Iwaszkiewicz-Eggebrecht et al, 2023;Marquina et al, 2022;Nielsen et al, 2019). However, there may be limitations relevant for the analysis of our samples: for instance, both Iwaszkiewicz-Eggebrecht et al (2023) and Marquina et al (2022) found that ants (Hymenoptera: Formicidae) were detected in their mock communities in much lower proportion and occasions than other taxa. This could have affected our results, as we worked with ground-dwelling arthropod communities, in which ants are prominent members.…”
Section: Biodiversity Detectionmentioning
confidence: 99%
“…Here, all calibration is based on comparison to a set of samples of known contents-and in support of one's findings, one would naturally report on the precision of one's measures. In metabarcoding, such calibration is typically made against a study-specific sample (or 'mock community'; [19][20][21]) of a composition purpose-invented by the laboratory in question. In the end, we face a high probability of comparing apples to oranges.…”
Section: Introductionmentioning
confidence: 99%